Pressing Questions of Historiography of Rus’-Hungarian Relations of the First Third of the XIII Century - Чугуй, Тарас (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The paper analyzes the interpretation of pressing questions of Rus’-Hungarian relations at the time of the prince Danylo Romanovich and the king Andriy II in historiography. Debatable aspects of the policy of Hungarian royal power concerning Galich-Volyn Rus’, the peculiarities of the interstate relations of Rus’, Hungary and Poland have been considered. The circumstances of the struggle of the Romanoviches for the farther heredity, the significance of a Hungarian factor in the activity of political rivals and opponents of Danylo Romanovich have been clarified. The conclusions about the role of Rus’-Hungarian relations in the history of Galich and Volyn lands during 1205–1235 have been drawn.